Factors affecting shrivelling and friction discolouration of pears (Pyrus communis L. ) - Burger, G. E. (Gerrit Erasmus) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric)--University of Stellenbosch, 2005.